ANALISIS KEMAMPUAN LITERASI TEKS INFORMASI DALAM PEMBELAJARAN BAHASA INDONESIA BERDASARKAN PROSES KOGNITIF PADA SISWA KELAS IV SDN 060926 MEDAN: Penelitian Kualitatif - Natasya Sihombing; Dian Armanto; Anita Yus (STKIP Subang, 2026)
This study aims to analyze the ability of fourth-grade students at SDN 060926 Medan to read and comprehend informational texts in Bahasa Indonesia learning, as measured through two learning objectives derived from the Grade IV Indonesian Language Curriculum. The first learning objective focuses on students' ability to identify the main ideas, key information, and factual content of informational texts, which is examined through three cognitive processes: understanding, application, and reasoning. The second learning objective focuses on students' ability to use, critically evaluate, and reflect on information from texts, examined through three cognitive processes: finding information, interpretation and integration, and evaluation and reflection. This study employs a qualitative descriptive approach with 20 Grade IV students as subjects, selected through purposive sampling. Data were collected through written tests, in-depth interviews, and documentation. Results indicate that students perform best on the understanding sub-aspect (70% proficient) under Learning Objective 1, and on finding information (65% proficient) under Learning Objective 2. The lowest performance was recorded on evaluation and reflection (35% proficient). These findings call for more varied and critical literacy instruction strategies in elementary schools.